Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1103/physrevlett.102.227201
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Universal and Topological Anomalous Hall Effects in MetalCrO2Thin Films in the Dirty Limit

Abstract: The scaling exponent of 1.6 between anomalous Hall and longitudinal conductivity, characteristic of the universal Hall mechanism in dirty-metal ferromagnets, emerges from a series of CrO 2 films as we systematically increase structural disorder. Magnetic disorder in CrO 2 increases with temperature and this drives a separate topological Hall mechanism. We find that these terms are controlled discretely by structural and magnetic defect populations, and their coexistence leads to apparent divergence from expone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…A strong correlation between the spins of localized and nonlocalized electrons makes the Hall effect and also the anomalous Hall effect a subtle tool to probe topological spin defects of the 3D ferromagnetic material. 13,14 The compound CrO 2 is a metastable phase and bulk material is synthesized at high pressures. Deposition techniques such as sputtering, pulsed laser deposition, or molecular beam epitaxy cannot be used, but high-quality thin films can be grown using the technique of chemical vapor deposition (CVD) at ambient pressure, as for instance discussed in Refs.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong correlation between the spins of localized and nonlocalized electrons makes the Hall effect and also the anomalous Hall effect a subtle tool to probe topological spin defects of the 3D ferromagnetic material. 13,14 The compound CrO 2 is a metastable phase and bulk material is synthesized at high pressures. Deposition techniques such as sputtering, pulsed laser deposition, or molecular beam epitaxy cannot be used, but high-quality thin films can be grown using the technique of chemical vapor deposition (CVD) at ambient pressure, as for instance discussed in Refs.…”
Section: Materials and Sample Preparationmentioning
confidence: 99%
“…Watts et al presented data showing a sign reversal at low temperatures, 12 which they interpreted as evidence for two-band transport, but this was not found in later studies. 13,14 In this article we return to the issue of magnetotransport in high-quality thin films of CrO 2 , with proper attention to the different crystallographic axes of the material. We find resistivity behavior that is subtly different from earlier reports, with an anomaly around 100 K. We do not see a sign change in the Hall effect reported in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Gupta et al 13 fit the low-temperature resistivity (below 40 K) with a ρ(T ) = ρ 0 + AT 3 dependence characteristic of spin-flip scattering if the non-rigid band behavior of the minority band is accounted for. Watts et al proposed a two-band picture for electronic conduction based on a magnetotransport study 14 , although other magnetoresistance studies have not reached the same conclusion 15,16 . Several authors found that a T 2 dependence also describes well the resistivity data in a broad temperature range and attributed this to electron-electron scattering 9,17 .…”
Section: Introductionmentioning
confidence: 99%
“…This mechanism produces an anomalous Hall signal called the topological Hall effect (14)(15)(16)(17).…”
mentioning
confidence: 99%